PT. Panca Manpowerindo Business Strategy To Overcome Future Challenges In Mining Industry - Ihsan, Aulia (The Indonesian Journal of Business Administration, 2014)
Abstract. In the era of globalization, and from the business standpoint capitalism already gripping throughout the life , and the nature of capitalism are expansive and exploitative, they also sounded â€œbusiness efficiencyâ€ so business every year can grow but it has a domino effect. PT Panca Manpowerindo established since 2009 and first began working with PT Newmont Nusa Tenggara. As manpower providers, PT PMP got their first job called â€œRelining projectâ€ where the task had routine maintenance on Concentrator - SAG Mill and Ball Mill area, in recent years the business has grown as a manpower provider and a provider of haul truck operator for some heavy vehicles that are supported by Trakindo.This final project is discussing about PT Panca Manpowerindo business strategy facing the uncertain conditions in the mining industry, PT Panca Manpowerindo needs to make quick decisions in the near future so the company can still operate and still make profit. Currently, the company running an outsourcing business that supply manpower to several mining company but along with internal and external conditions in the business environment, PT PMP thinking to diversify their business by applying market development strategies and product development strategies, so PT Panca Manpowerindo not only can survive and has business continuity, but also can remain competitive in the mining industry that is currently in a period of downturn due to the enactment of UU No. 4 of 2009 on Mineral and Coal, which prohibits the export of raw minerals for some types of commodities..Â Keywords : Business strategy,Diversification / Product - Market matrix strategy, Generic Competitive strategy